(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
This study article aims to comprehend the marketing strategies used by fast-movingconsumer goods (FMCG) industry for processed food and drinks. Between 18 and 19 of revenues inthe FMCG sector are made up of food and beverage goods. Food that has been processed is becoming asignificant sector of the FMCG industry. All around India, there are sizable food processing industries.According to numerous projections, FMCG companies’ revenue is anticipated to exceed 53by 2025. Oneof the food industry segments with the fastest growth rates worldwide is fast food. Fast food culture did,however, become more popular in India over time as a result of the expansion of nuclear families,economic growth, rising per capita income, and globalisation. According to the report, 64 ofrespondent‘s frequent fast food restaurants once a week, the majority of respondents spend more than15 of their monthly income on fast food, and western junk food is the respondents’ preferred cuisine.Additionally, they stated that the discounts provided at fast food restaurants are thought to be anefficient kind of advertising. Large corporations dominate the fiercely competitive fast food sector.